The Effect Of Advertising, Sales Promotion, And Brand Image On Repurchasing Intention (Study On Shopee Users) - Azmi, Maulida; S. Shihab, Muchsin; Rustiana, Deden; Indra; Lazirkha, Diana Putri (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2022)
The background of this research comes from the current trend of online shopping as nowadays online shopping is often used by consumers. One of the top brands in e-commerce is Shopee, although Shopee have many visitors, but it does not reflect the high repurchase intention that can be seen from the value of the Shopee transaction. Therefore, it is important for companies to know the factors that influence the repurchase intention from Shopee. The purpose of this study is to find out the factors that affect repurchase intention in consumers using Shopee applications through advertisements, sales promotions, and brand image. This type of research is quantitative research. The data presented in this study were obtained through a questionnaire given to 110 respondents. Statistical analysis using SPSS 16 is used in the model and hypothesis testing. The results of this study indicate that advertising, sales promotion, and brand image have a positive effect on repurchase intention in Shopee.